Atividades curriculares de integração ensino, pesquisa e extensão na Universidade Federal de São Carlos : práticas e significados à luz de Paulo Freire - Gomes, Geraldo Biason (Universidade Federal de São Carlos, 2016)
University Extention initiatives have been growing in importance concerning the articulation between universities and society, and also academic efforts from universities themselves regarding their relationship with teaching and research. Teaching, Research and Extention Integration of Curricular Activities (ACIEPEs in Portuguese) at the Federal University of São Carlos (UFSCar), Brazil are intervention projects that contribute to university extention efforts, consisting of multidisciplinary teams and involving teachers, technicians and students from the university, which are open to the external community to participate. The aim of this study was to verify if the ACIEPEs meet the objective they propose, especially regarding the integration of the university with the external public and promoting access to knowledge, aiming to motivate the external public to participate. Among the various possibilities of research focus suggested by the diversity of subjects addressed by the ACIEPEs, Paulo Freire´s view on Extention was used, considering the current relevance and great contribution of his work to Education in general, and especially Extention. It also sought to determine which Freirean references or alignment points between the characteristics of the ACIEPEs and Freirean references are found in the ACIEPEs practice. This study is based on bibliographical and documentary research, with data collect through questionnaire and interview, followed by content analysis. As a result, it was found: 1. that some alignment points between Freire´s view on Extention and characteristics of the ACIEPEs appear to be diffuse across many of the references in Freire´s work and the outcome desired by the ACIEPEs; 2. whereby the ACIEPEs meet their objectives, including: a) providing a wideranging training program to students at UFSCar encouraging them to have critical insight that goes beyond obtaining technical knowledge; b) providing an enriching experience to the various actors involved - students, teachers and the external public; c) collaborating with institutional goals of university integration with the external public and promoting access to knowledge; and d) acting on the principle of indivisibility between teaching, research and extention; and 3. making it possible to identify a successful training model, as well as dissemination, production and knowledge reconstruction from the ACIEPEs, suggesting guidelines to adopt this model in traditional undergraduate subjects.
Keywords: ACIEPE; Extensão universitária; Acesso ao conhecimento; Produção de conhecimento; Paulo Freire; University extension; Access to knowledge.; Knowledge production; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA